Pengaruh Rasa Percaya Diri Guru Terhadap Proses Belajar Mengajar di Sekolah - Syafrizal Syafrizal (Serambi Tarbawi, 2023)
This discussion aims to examine the effect of teacher self-confidence on the teaching and learning process in schools. Teacher self-confidence is a key factor in educational success, because confident teachers tend to be more effective in conveying subject matter and motivating students to learn better. Teachers who have a high level of self-confidence tend to be more courageous in taking initiatives, being creative in presenting material, and more prepared to face challenges in managing the classroom. In addition, teacher self-confidence also has a positive impact on student motivation, where students tend to be more motivated to learn and participate actively in the learning process. Even so, there are several factors that can affect the level of teacher confidence, such as level of education and teaching experience. Teachers with higher formal education and more extensive teaching experience tend to have more confidence in dealing with complex classroom situations. In the context of improving the education system, it provides valuable information for schools and educational institutions to improve teacher competence and help increase their self-confidence. Professional training and development can be an effective strategy to increase teacher self-confidence, so that it can have a positive impact on the quality of the teaching and learning process in schools. In addition, an interactive approach between teachers and students and a supportive educational environment can also play an important role in increasing teacher confidence and the overall quality of learning.